2010
DOI: 10.1016/j.trstmh.2010.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for community-acquired hepatitis C infection from birth to 5 years of age in rural Egyptian children

Abstract: A prospective study in three Egyptian villages (A, B and C) having a high prevalence of hepatitis C virus (HCV) infection examined incidence of community-acquired HCV infection in children; 2852 uninfected infants were prospectively followed from birth for up to 5.5 years. Fifteen seroconverted for either HCV antibodies and/or HCV-RNA (incidence of 0.53%). Ten had both anti-HCV and HCV-RNA; four had only anti-HCV; and one had HCV-RNA in the absence of antibody. The incidence rate at all ages was 2.7/1000 perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…Saleh et al reported a greater risk for incident infection among women whose babies were delivered by a physician rather than by a nurse or a traditional birth attendant, in a health facility rather than at their home, and in women having complicated vaginal deliveries [15]. Among children, incident infection was associated with hospitalization and low birth weight [17]. Community and informal health provider related exposures such as circumcision, cautery, and injections were also associated with HCV infection [62,82,120].…”
Section: Resultsmentioning
confidence: 99%
“…Saleh et al reported a greater risk for incident infection among women whose babies were delivered by a physician rather than by a nurse or a traditional birth attendant, in a health facility rather than at their home, and in women having complicated vaginal deliveries [15]. Among children, incident infection was associated with hospitalization and low birth weight [17]. Community and informal health provider related exposures such as circumcision, cautery, and injections were also associated with HCV infection [62,82,120].…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that prolonged hospitalization and low birth weight increased the risk of infection, whereas maternal HCV was the source of infection in only two older children. By the end of the followup period, six children (40%) had natural clearance [39] . A fouryear populationbased cohort study was conducted on seronegative villagers to calculate the incidence of new HCV cases.…”
Section: Incidencementioning
confidence: 99%
“…However, most studies have found that blood transfusion is no longer a risk factor for HCV in pregnancy [50,104], and the same is generally true in Arab countries [24], although some Arab countries have found it to be a risk factor [50]. In contrast, blood transfusion might well be a risk factor among African countries, such as Ghana and Kenya, and probably a number of others, because of budget shortfalls [105,106,107].…”
Section: Factors Associated With Transmission Of Hcv Among Pregnant Wmentioning
confidence: 99%
“…Another sociodemographic factor of concern is educational level. It has been found that women who have received less than secondary school level education are at higher risk [24], and an Egyptian group has found that a low level of maternal education is a risk factor for HCV infection of children [106]. Being the long-term steady sex partner of an HCVinfected individual is not a risk factor [108], as the role of sexual transmission itself in HCV infection needs validation [109].…”
Section: Sociodemographic Factorsmentioning
confidence: 99%